2017
DOI: 10.1039/c7cc02789c
|View full text |Cite
|
Sign up to set email alerts
|

Identification of actin as a direct proteomic target of berberine using an affinity-based chemical probe and elucidation of its modulatory role in actin assembly

Abstract: Despite the diverse pharmacological activities of berberine, including anti-cancer and anti-inflammatory effects, the direct proteomic targets of berberine have remained largely unknown. Here, we have identified actin as a direct proteomic target of berberine using an affinity-based chemical probe. In addition, we found that actin assembly was significantly modulated by berberine in vitro at the biochemical level and cellular level.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…Taking NEK7 kinase as a target for screening, novel NEK7–NLRP3 interaction inhibitors might be easily achieved to combat various inflammation-related diseases. As a multitarget natural product, several other direct proteomic targets of BBR, such as UHRF1, RXRα, actin, and ephrin-B2, have been identified to explain its multiple pharmacological activities, including the anticancer activity. Therefore, these findings provide an important explanation to achieve a comprehensive understanding and interpretation of BBR’s polypharmacological activities and its natural evolution. Our results fully support NEK7 as one of the key direct targets of BBR with multipharmacological efficacy, and verification of other direct target proteins of BBR with effects against inflammation is actively underway.…”
Section: Discussionmentioning
confidence: 99%
“…Taking NEK7 kinase as a target for screening, novel NEK7–NLRP3 interaction inhibitors might be easily achieved to combat various inflammation-related diseases. As a multitarget natural product, several other direct proteomic targets of BBR, such as UHRF1, RXRα, actin, and ephrin-B2, have been identified to explain its multiple pharmacological activities, including the anticancer activity. Therefore, these findings provide an important explanation to achieve a comprehensive understanding and interpretation of BBR’s polypharmacological activities and its natural evolution. Our results fully support NEK7 as one of the key direct targets of BBR with multipharmacological efficacy, and verification of other direct target proteins of BBR with effects against inflammation is actively underway.…”
Section: Discussionmentioning
confidence: 99%
“…The residue was purified over silica gel CC using DCM/methanol (20 : 1, 15 : 1, and 10 : 1) as eluent to give the red solid compounds 6 -10. (7). Yield: 38.1 %.…”
Section: Synthetic Procedures Of Compounds 6-10mentioning
confidence: 98%
“…Natural products have been being an important source to develop effective therapeutic agents against diseases, including cancers. [6,7] Natural quaternary protoberberine alkaloids (QPAs) with the shared core structure of 5,6-dihydroisoquinolino[3,2-a]isoquinolin-7-ium chloride are a class of famous compounds born of several plant species, such as Coptis chinensis of Ranunculaceae. [8,9] The elucidation of the biological activities of QPAs has paved a way to regard them as 'dreamt molecules' in the field of medicinal chemistry to be studied to guide the development of related therapeutic agents.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Yi et al. reported that berberine directly bound to actin and inhibited the migration of mouse mononuclear macrophage leukemia cells and mouse embryonic fibroblasts ( Yi et al., 2017 ). However, the direct binding targets investigated in previous studies are not sufficient to elucidate the role of berberine in improving the metabolic reprogramming of colorectal cancer.…”
Section: Introductionmentioning
confidence: 99%